Effect of institutional quality and foreign direct investment on economic growth and environmental quality: evidence from African countries. Issue 1 (31st December 2022) - Wang, Mei Ling; Ntim, Vincent Sarkodie; Yang, Jiameng; Zheng, Qiongjie; Geng, Limin
Abstract: This study applies the method of the fully modified ordinary least squares (FMOLS) method and the vector error correction model (VECM) to explore whether institutional quality (IQ) and foreign direct investment (FDI) promoted economic growth (EG) and environmental quality (EQ) in oil-producing and non-oil-producing African countries from 1999 to 2017. The FMOLS findings demonstrate that IQ significantly promoted EG and improved EQ in the non-oil-producing countries, however it only improved EQ and showed no significant impact on EG in oil-producing countries. FDI significantly promoted EG to a higher extent in oil-producing countries than in non-oil-producing countries, but it presented no significant impact on EQ in both groups. The VECM results reveal that (i) two-way causation among IQ and EG, IQ and EQ, FDI and EG, and FDI and EQ was occurred in both groups, in the long-run. (ii) two-way causation among FDI and EQ and one-way causation from FDI to EG was observed in non-oil-producing countries in the short-run. Moreover, two-way causation among IQ and EG, and one-way causation from IQ to EQ were observed in non-oil-producing countries. To realize the sustainable development of economy and environment, a series of policy suggestions have been discussed.